Mental health in a post-pandemic perspective: economic and social costs - Juraszek, Paweł; Karolina, Sobczyk; Grajek, Mateusz (Journal of Education, Health and Sport, 2024)
The COVID-19 pandemic has caused a significant increase in the number of mental health disorders, such as depression, anxiety, and PTSD, leading to higher treatment costs and placing a burden on social insurance systems. The aim of this literature review was to examine the economic costs of the pandemic related to mental health and assess its impact on social insurance systems. The review also analyzed the growing demand for mental health services during different phases of the pandemic. The methodology included an analysis of scientific literature from 2020-2023, with sources from databases like PubMed, Scopus, and JSTOR. The focus was on studies that provided a detailed examination of the economic aspects of the pandemic in the context of mental health, including both direct costs (consultations, medications) and indirect costs (reduced productivity, work absences). The findings indicate significant economic burdens for both healthcare and social insurance systems. The COVID-19 pandemic has increased the cost of treating mental health disorders globally. Both WHO and OECD highlight that global indirect costs related to lost productivity amount to approximately 1 trillion annually. Additionally, the pandemic exposed weaknesses in social insurance systems, which need to be reformed to address new health challenges. Key conclusions emphasize the need for further investment in mental health care, particularly in prevention and early intervention. Such investments could lead to significant economic savings by reducing treatment costs and improving productivity. Reforming social insurance systems is also recommended to better accommodate the needs of individuals suffering from mental health disorders.